Revisiting Fair Dealing and Copyright Infringement in India vis-à-vis Research and Education - Tiwari, Himanshi; Singh, Anant Kumar (DESIDOC Journal of Library & Information Technology, 2025)
Copyright law grants authors and creators an “exclusive right” to their original works while allowing certain exceptions that enable individuals to use these works in ways that would typically infringe copyright. This exception is known as the “doctrine of fair use” in the United States and the “doctrine of fair dealing” in India. These doctrines encompass the ‘permitted acts’ or ‘defences’ recognised by copyright laws across various jurisdictions. ‘Fair dealing’ and copyright are intrinsically linked and cannot exist in isolation. In India, Section 52 of the Copyright Act of 1957 outlines the provisions associated with “fair dealing” and enumerates possible defences against copyright infringement claims. The primary objective of ‘fair dealing’ is to foster research and education; however, its overly restrictive nature has hindered the achievement of this goal. The limited scope of ‘fair dealing’ provision and judgments, which lack clarity and certainty, fail to address the challenges faced by developing nations like India, where access to information remains a significant barrier to progress. This paper intends to thoroughly examine the existing legal principles and jurisprudence surrounding this doctrine in the context of research and education in India, highlighting the challenges it faces and proposing potential reforms to revise copyright law to enhance both its flexibility and predictability within the context of India’s socio-economic landscape and to foster research and education.